Pharmacy student professional identity formation: a scoping review - Noble C; McKauge L; Clavarino A (Dove Medical Press, 2019)
Christy Noble,1–3 Leigh McKauge,3 Alexandra Clavarino3 1Allied Health, Clinical Governance, Education and Research, Gold Coast Health, Southport, QLD, Australia; 2School of Medicine, Griffith University, Parkwood, QLD, Australia; 3School of Pharmacy, The University of Queensland, Woolloongabba, QLD, Australia Purpose: Transitioning from being pharmacy students to pharmacists is challenging. Students need to reconcile their professional aspirations and what they have learnt with the realities of practice. A smooth transition can be hampered when they are unable to enact the role they have envisaged or if their expectations are not met. These challenges relate to professional identity. A key challenge for pharmacy educators is how best to support the professional identity formation (PIF) of pharmacy students. To assist with this challenge, we conducted a scoping review to identify factors influencing pharmacy students’ PIF and pedagogical strategies to support PIF.Methods: In September 2018, we undertook a scoping review of all contemporary research investigating pharmacy student PIF including all relevant qualitative, quantitative, theoretical, and gray literature. We searched eight databases for the review: MEDLINE, CINAHL, PsycINFO, Embase, Australian Education Index, PubMed, Scopus, and Web of Science. Literature published between January 2008 and September 2018 was reviewed and screened using inclusion/exclusion criteria. The selected articles were charted and thematically analyzed.Results: We included 22 articles in the review. Studies generally concurred about the importance of attending to PIF throughout the whole pharmacy curriculum. Yet, those studies reporting on pharmacy students’ professional identities found that students experienced challenges forming their identities. While several curriculum interventions supporting PIF have been implemented, these tended to be one-offs and there was an absence of interventions engaging key stakeholders including placement preceptors, other health professionals, and patients/consumers.Conclusion: Supporting the formation of pharmacy students’ professional identity, while recognized as an important goal for pharmacy education, requires further empirical inquiry. Pedagogical practices focused on identity formation including adopting an integrative curricular approach are required. Keywords: pharmacy education, curriculum, social identification, health professionals